Visible‐Light Photocatalytic Reduction of CO2 to Formic Acid with a Ru Catalyst Supported by N, N′‐Bis(diphenylphosphino)‐2, 6‐diaminopyridine Ligands. Issue 15 (3rd July 2019) - Hameed, Yasmeen; Rao, Gyandshwar Kumar; Ovens, Jeffrey S.; Gabidullin, Bulat; Richeson, Darrin
Abstract: Visible‐light photocatalytic CO2 reduction is carried out by using a Ru II complex supported by N, N ′‐bis(diphenylphosphino)‐2, 6‐diaminopyridine ("PNP") ligands, an unprecedented molecular architecture for this reaction that breaks the longstanding domination of α‐diimine ligands. These competent catalysts transform CO2 into formic acid with high selectivity and turnover number. A proposed mechanism, with combined electron transfer and catalytic cycles, models the experimental rate of formic acid production. Abstract : Diimines aren't forever : A new molecular architecture for Ru II visible‐light CO2 reduction photocatalysts has been developed. These catalysts are supported by N, N ′‐bis(diphenylphosphino)‐2, 6‐diaminopyridine ligands and transform CO2 into formic acid with high selectivity and turnover number. A proposed mechanism successfully models the experimental rate of formic acid production.